Development of Value Added Kalakand Using Papaya Fruit - Manilal, Patel Kartikkumar; Roy, S K (Indian Journal of Dairy Science, 2015)
In recent years, there has been growing interest in the manufacture of value added products like kalakand and other khoa based product individually and/or fortified with fruits in buffalo milk. Kalakand is one of the most popular indigenous products of the country. It is a partially desiccated milk product with caramelized flavour and granular texture prepared from acidified milk and found to be an attractive product amongst all the classes of consumers. The present study has been carried out to study the effects of per cent replacement of buffalo milk by papaya pulp at different levels (5, 10, 15 and 20 % ) in the manufacture of kalakand. The final products were evaluated for sensory and chemical qualities. A 5 % and 20 % replacement by papaya pulp in buffalo milk was essential to obtain kalakand with satisfactory overall acceptability. Along with increase percentage of papaya pulp, the total solid percentage, fat percent, protein percent ash percent and acidity decreased and Carbohydrate percent increase.